Effect of aromatic herbs and roasted coconut flesh on acceptability and perception of mixed porridge (bubur paddas) - Risa Nofiani; Puji Ardiningsih; Hendra Perdana; Isam Alatin; Kutsiatul Hasanah; Irine Fajrin Roeswandi; Leni Juniarti; Nurul Huda (Agroindustrial Technology, University of Trunojoyo Madura, 2025)
Bubur pedas or bubor paddas (BP) is porridge from roasted rice granules (R) rich in vegetables with a specific aroma that probably contributed to producing the aroma were roasted coconut flesh granules (C ), fresh kesum (Polygonum minus Huds) leaves (K), fresh buas-buas (Premna cordifolia ROXB) leaves (B), and fresh young tumeric (Curcuma longa) leaves (T). This study aimed to find out the effect of aroma-contributing ingredients (B, C, K, and T) and their role in developing specific aromas based on sensory panelists' acceptability and perception. Each aromatic ingredient was prepared in four serial formulations, namely C, K, B, and T, and a sensory test was then conducted using a hedonic rating method with a 9-point hedonic scale by a panel of 100-200 semi-trained panelists. The data were analyzed using a hierarchical analytical process (AHP), principle component analysis (PCA) biplot, multidimensional scaling (MDS) with alternating least squares scaling (ALSCAL) model, and Spearman's correlation. The highest acceptability for each aromatic ingredient's formula was 25 g of the C formula, 16 g of the K formula, 12 g of the B formula, and 12 g of the T formula, respectively. Almost the best formula for each aromatic ingredient's formula showed no correlation or dissimilarity. Among the aromatic ingredients, K and T played a pivotal role in developing the aroma, but only K enhanced the savory. Therefore, K and T were considered compulsory ingredients in generating a unique characteristic for BP in the panellists's perception